2018
DOI: 10.12991/jrp.2018.117
|View full text |Cite
|
Sign up to set email alerts
|

Aphrodisiac properties of Aquilaria malaccensis leaves aqueous extract in ICR mice

Abstract: The study was conducted to investigate the effects of Aquilaria malaccensis leaves aqueous extracts on the aphrodisiac properties, which included; sexual behaviour, orientation activity, and testosterone level in ICR mice. Thirty healthy and sexually experienced male and thirty non-estrous female mice were used. In this experiment, each male was cohabitated with one female in a polysulfone cage. The mice were divided into 6 groups that received normal saline (control group), 50 mg/kg, 100 mg/kg, 200 mg/kg, 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Previous studies also have reported the presence of steroids, flavonoids, triterpenoids, tannins and alkaloids in methanol leaves extract of A. malaccensis ( Nik et al 2014 ). A phytochemical finding also revealed the presence of flavonoid glycosides, 2-(2-phenylethyl) chromenes, lignans and diterpenoids in this plant extract ( Musa et al 2019 ). Numerous studies have been performed to examine the possible use of the extracts in diabetes care, arthritis, infection, inflammation, oxidation stress and cancer ( Zulkifle et al 2018 ; Hegde et al 2018 ; Mokhtar et al 2021 ).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies also have reported the presence of steroids, flavonoids, triterpenoids, tannins and alkaloids in methanol leaves extract of A. malaccensis ( Nik et al 2014 ). A phytochemical finding also revealed the presence of flavonoid glycosides, 2-(2-phenylethyl) chromenes, lignans and diterpenoids in this plant extract ( Musa et al 2019 ). Numerous studies have been performed to examine the possible use of the extracts in diabetes care, arthritis, infection, inflammation, oxidation stress and cancer ( Zulkifle et al 2018 ; Hegde et al 2018 ; Mokhtar et al 2021 ).…”
Section: Introductionmentioning
confidence: 81%
“…Although there were studies conducted on rats to determine the effects of A. malaccensis leaves aqueous extract (0.1 g/kg–1.0 g/kg) on male sexual behaviour, sperm fertilising capacity and ameliorative effects on male reproductive toxicity, there is still lack of information and insufficient scientific investigation on its effect on male fertility and reproductive function ( Ismail et al 2019 ; Musa et al 2019 ; Razak et al 2019a ; 2019b ). Therefore, this study was conducted to determine the effect of A. malaccensis leaves aqueous extract on weight of reproductive organs and sperm quality on adult male of Sprague Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…As several species of Ferula genus have been used in folk medicine as aphrodisiac, this study firstly examined the effect of the FHM extracts on the sexual efficiency of male rats including ML, IL, MF, and IF. Generally, MF and ML reflect sexual interest or libido, whereas the IF and IL are useful indices of the sexual excitement and the efficiency of erection (Ågmo, 1997;Che Musa et al, 2018). Sildenafil citrate was used as positive reference drug.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in developing nations have been driven to seek traditional plant medicine, also known as phytotherapy, due to their inability to afford contemporary medical treatment for infertility. Medicinal plants with aphrodisiac characteristics have been used to treat a variety of male infertility issues (Che Musa et al, 2018). Phytotherapy is gaining popularity in the community since it is natural, inexpensive, has fewer side effects, is easy to use, and has a positive therapeutic outcome (Kotta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%